2010
DOI: 10.1051/epjconf/20100611001
|View full text |Cite
|
Sign up to set email alerts
|

Single point incremental sheet forming investigated by in-process 3D digital image correlation

Abstract: Abstract. Single Point Incremental Forming (SPIF) is a promising sheet metal forming process for prototyping and small batches, in which the blank is formed in a stepwise fashion by a displacement-controlled small-sized tool. Due to specific strain paths induced by the process and limited plastic zones in the contact region between the tool and the workpiece, forming diagrams and forming strategies are different from the classical stamping processes. One major limitation of SPIF is the lack of accuracy of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Formability in SPIF can be defined by the maximum wall angle (see Fig. 4), and it is measured in terms of a tangent line from the unformed blank to the deformed part of the surface, determined by sine law, t f = t i sin(π/2 − ) = t i sinα, where t i and t f are the initial and final thicknesses of the part, respectively, and α is the semicone angle [19]. Thus, max is usually used as a parameter to measure whether the SPIF Fig.…”
Section: Formability In Spifmentioning
confidence: 99%
See 1 more Smart Citation
“…Formability in SPIF can be defined by the maximum wall angle (see Fig. 4), and it is measured in terms of a tangent line from the unformed blank to the deformed part of the surface, determined by sine law, t f = t i sin(π/2 − ) = t i sinα, where t i and t f are the initial and final thicknesses of the part, respectively, and α is the semicone angle [19]. Thus, max is usually used as a parameter to measure whether the SPIF Fig.…”
Section: Formability In Spifmentioning
confidence: 99%
“…The effect of some parameters, such as step size, on the formability of a commercially pure titanium blank was investigated by Hussain et al [44], and the results proved that the formability decreases linearly as the step size increases. Experimental investigation by means of surface 3D digital image correlation was published by Decultot et al [19] in forming of an AW-5086-H111-grade aluminium alloy. It was found that the workpiece formability was reduced with the increase of increment step size.…”
Section: Incremental Depth (Step Size)mentioning
confidence: 99%
“…Experimental observations show that fracture is not preceded by localised necking and cracks develop by tensile meridional stresses under stretching conditions but not by plane shear stresses. An experimental work using a surface 3D digital image correlation showed that the fracture occurred in the uniaxial stretching domain [3].…”
Section: Introductionmentioning
confidence: 99%
“…When the load increases and reaches the maximum value (3.04 KN), and displacement reaches (11 mm), significant changes in the dimensions of the tensile specimen can be noticed. Furthermore, the material 04013-p. 4 ICNFT 2015 bearing capacity is quickly lost and the void volume fraction reaches the critical value f c (0.2593) (Fig. 3C).…”
Section: Determination Of Materials Parameters Of the Gtn Modelmentioning
confidence: 99%
“…Experimental observations show that the fracture is not preceded by localized necking and the crack develops under tensile meridional stresses acting under stretching conditions and not by plane shearing stresses. An experimental work using a surface 3D digital image correlation showed that the fracture occurred in the uniaxial stretching domain [4]. To predict the occurrence of failure in the AA5052 sheet, Malhotra et al [5,6] used explicit FEA with a damage-based fracture model, in which the failure envelope depends on the hydrostatic pressure and the lode angle.…”
Section: Introductionmentioning
confidence: 99%